Debate position: cognition and mood are not improved in men administered exogenous testosterone therapy. Issue 6 (November 2017) - Yalamanchi, Swaytha; Dobs, Adrian
Abstract : Purpose of review: The purpose of this article is to provide an overview of the increasing evidence suggesting that exogenous testosterone therapy is not associated with improvements in cognition or mood. This article is part of a series, in this issue, in which authors are assigned opinion pieces on controversial topics pertaining to testosterone replacement. Recent findings: Testosterone is increasingly being prescribed. Particularly in the setting of recent data suggestive of possible cardiovascular risk associated with its use; a clear understanding of the domains of health that improve with exogenous testosterone use is important. Data on endogenous and exogenous testosterone with cognition and mood are mixed, likely partly related to methodological differences of type of testosterone, patient population, and dosing. Summary: Overall, available data are not suggestive of a clear benefit of testosterone supplementation in multiple domains of cognition and in mood. Supraphysiologic testosterone has been associated with adverse psychological outcomes, albeit not uniformly in studies.